Algebra and Trigonometry

# Chapter 9

Algebra and TrigonometryChapter 9

### 9.1Verifying Trigonometric Identities and Using Trigonometric Identities to Simplify Trigonometric Expressions

1.
$cscθcosθtanθ = ( 1 sinθ )cosθ( sinθ cosθ ) = cosθ sinθ ( sinθ cosθ ) = sinθcosθ sinθcosθ = 1 cscθcosθtanθ = ( 1 sinθ )cosθ( sinθ cosθ ) = cosθ sinθ ( sinθ cosθ ) = sinθcosθ sinθcosθ = 1$
2.
$cotθ cscθ = cosθ sinθ 1 sinθ = cosθ sinθ ⋅ sinθ 1 = cosθ cotθ cscθ = cosθ sinθ 1 sinθ = cosθ sinθ ⋅ sinθ 1 = cosθ$
3.

$sin 2 θ−1 tanθsinθ−tanθ = (sinθ+1)(sinθ−1) tanθ(sinθ−1) = sinθ+1 tanθ sin 2 θ−1 tanθsinθ−tanθ = (sinθ+1)(sinθ−1) tanθ(sinθ−1) = sinθ+1 tanθ$

4.

This is a difference of squares formula: $25−9 sin 2 θ=(5−3sinθ)(5+3sinθ). 25−9 sin 2 θ=(5−3sinθ)(5+3sinθ).$

5.
$cosθ 1+sinθ ( 1−sinθ 1−sinθ ) = cosθ(1−sinθ) 1− sin 2 θ = cosθ(1−sinθ) cos 2 θ = 1−sinθ cosθ cosθ 1+sinθ ( 1−sinθ 1−sinθ ) = cosθ(1−sinθ) 1− sin 2 θ = cosθ(1−sinθ) cos 2 θ = 1−sinθ cosθ$

### 9.2Sum and Difference Identities

1.

$2 + 6 4 2 + 6 4$

2.

$2 − 6 4 2 − 6 4$

3.

$1− 3 1+ 3 1− 3 1+ 3$

4.

$cos( 5π 14 ) cos( 5π 14 )$

5.
$tan(π−θ) = tan(π)−tanθ 1+tan(π)tanθ = 0−tanθ 1+0⋅tanθ = −tanθ tan(π−θ) = tan(π)−tanθ 1+tan(π)tanθ = 0−tanθ 1+0⋅tanθ = −tanθ$

### 9.3Double-Angle, Half-Angle, and Reduction Formulas

1.

$cos( 2α )= 7 32 cos( 2α )= 7 32$

2.

$cos 4 θ− sin 4 θ=( cos 2 θ+ sin 2 θ )( cos 2 θ− sin 2 θ )=cos( 2θ ) cos 4 θ− sin 4 θ=( cos 2 θ+ sin 2 θ )( cos 2 θ− sin 2 θ )=cos( 2θ )$

3.

$cos( 2θ )cosθ=( cos 2 θ− sin 2 θ )cosθ= cos 3 θ−cosθ sin 2 θ cos( 2θ )cosθ=( cos 2 θ− sin 2 θ )cosθ= cos 3 θ−cosθ sin 2 θ$

4.

5.

$− 2 5 − 2 5$

### 9.4Sum-to-Product and Product-to-Sum Formulas

1.

$1 2 ( cos6θ+cos2θ ) 1 2 ( cos6θ+cos2θ )$

2.

$1 2 ( sin2x+sin2y ) 1 2 ( sin2x+sin2y )$

3.

$−2− 3 4 −2− 3 4$

4.

$2sin( 2θ )cos( θ ) 2sin( 2θ )cos( θ )$

5.

$tanθcotθ− cos 2 θ = ( sinθ cosθ )( cosθ sinθ )− cos 2 θ = 1− cos 2 θ = sin 2 θ tanθcotθ− cos 2 θ = ( sinθ cosθ )( cosθ sinθ )− cos 2 θ = 1− cos 2 θ = sin 2 θ$

### 9.5Solving Trigonometric Equations

1.

$x= 7π 6 , 11π 6 x= 7π 6 , 11π 6$

2.

$π 3 ±πk π 3 ±πk$

3.

$θ≈1.7722±2πk θ≈1.7722±2πk$ and $θ≈4.5110±2πk θ≈4.5110±2πk$

4.

$cosθ=−1,θ=π cosθ=−1,θ=π$

5.

$π 2 , 2π 3 , 4π 3 , 3π 2 π 2 , 2π 3 , 4π 3 , 3π 2$

### 9.1 Section Exercises

1.

All three functions, $F F$,$GG$, and $H H$, are even.

This is because $F( −x )=sin( −x )sin( −x )=( −sinx )( −sinx )= sin 2 x=F( x ) F( −x )=sin( −x )sin( −x )=( −sinx )( −sinx )= sin 2 x=F( x )$,$G( −x )=cos( −x )cos( −x )=cosxcosx= cos 2 x=G( x ) G( −x )=cos( −x )cos( −x )=cosxcosx= cos 2 x=G( x )$ and $H( −x )=tan( −x )tan( −x )=( −tanx )( −tanx )= tan 2 x=H( x ). H( −x )=tan( −x )tan( −x )=( −tanx )( −tanx )= tan 2 x=H( x ).$

3.

When $cost=0, cost=0,$ then $sect= 1 0 , sect= 1 0 ,$ which is undefined.

5.

$sinx sinx$

7.

$secx secx$

9.

$csct csct$

11.

$−1 −1$

13.

$sec 2 x sec 2 x$

15.

$sin 2 x+1 sin 2 x+1$

17.

$1 sinx 1 sinx$

19.

$1 cotx 1 cotx$

21.

$tanx tanx$

23.

$−4secxtanx −4secxtanx$

25.

$± 1 cot 2 x +1 ± 1 cot 2 x +1$

27.

$± 1− sin 2 x sinx ± 1− sin 2 x sinx$

29.

$cosx− cos 3 x = cosx(1− cos 2 x) = cosx sin 2 x cosx− cos 3 x = cosx(1− cos 2 x) = cosx sin 2 x$

31.

$1+ sin 2 x cos 2 x = 1 cos 2 x + sin 2 x cos 2 x = sec 2 x+ tan 2 x= tan 2 x+1+ tan 2 x=1+2 tan 2 x 1+ sin 2 x cos 2 x = 1 cos 2 x + sin 2 x cos 2 x = sec 2 x+ tan 2 x= tan 2 x+1+ tan 2 x=1+2 tan 2 x$

33.

$cos 2 x− tan 2 x=1− sin 2 x−( sec 2 x−1 )=1− sin 2 x− sec 2 x+1=2− sin 2 x− sec 2 x cos 2 x− tan 2 x=1− sin 2 x−( sec 2 x−1 )=1− sin 2 x− sec 2 x+1=2− sin 2 x− sec 2 x$

35.

False

37.

False

39.

Proved with negative and Pythagorean identities

41.

True $3 sin 2 θ+4 cos 2 θ=3 sin 2 θ+3 cos 2 θ+ cos 2 θ=3( sin 2 θ+ cos 2 θ )+ cos 2 θ=3+ cos 2 θ 3 sin 2 θ+4 cos 2 θ=3 sin 2 θ+3 cos 2 θ+ cos 2 θ=3( sin 2 θ+ cos 2 θ )+ cos 2 θ=3+ cos 2 θ$

### 9.2 Section Exercises

1.

The cofunction identities apply to complementary angles. Viewing the two acute angles of a right triangle, if one of those angles measures $x, x,$ the second angle measures $π 2 −x. π 2 −x.$ Then $sinx=cos( π 2 −x ). sinx=cos( π 2 −x ).$ The same holds for the other cofunction identities. The key is that the angles are complementary.

3.

$sin( −x )=−sinx, sin( −x )=−sinx,$ so $sinx sinx$ is odd. $cos( −x )=cos( 0−x )=cosx, cos( −x )=cos( 0−x )=cosx,$ so $cosx cosx$ is even.

5.

$2 + 6 4 2 + 6 4$

7.

$6 − 2 4 6 − 2 4$

9.

$−2− 3 −2− 3$

11.

$− 2 2 sinx− 2 2 cosx − 2 2 sinx− 2 2 cosx$

13.

$− 1 2 cosx− 3 2 sinx − 1 2 cosx− 3 2 sinx$

15.

$cscθ cscθ$

17.

$cotx cotx$

19.

$tan( x 10 ) tan( x 10 )$

21.

$sin(a−b) = ( 4 5 )( 1 3 )−( 3 5 )( 2 2 3 ) = 4−6 2 15 cos(a+b) = ( 3 5 )( 1 3 )−( 4 5 )( 2 2 3 ) = 3−8 2 15 sin(a−b) = ( 4 5 )( 1 3 )−( 3 5 )( 2 2 3 ) = 4−6 2 15 cos(a+b) = ( 3 5 )( 1 3 )−( 4 5 )( 2 2 3 ) = 3−8 2 15$

23.

$2 − 6 4 2 − 6 4$

25.

$sinx sinx$

27.

$cot( π 6 −x ) cot( π 6 −x )$

29.

$cot( π 4 +x ) cot( π 4 +x )$

31.

$sinx 2 + cosx 2 sinx 2 + cosx 2$

33.

They are the same.

35.

They are the different, try $g( x )=sin( 9x )−cos( 3x )sin( 6x ). g( x )=sin( 9x )−cos( 3x )sin( 6x ).$

37.

They are the same.

39.

They are the different, try $g( θ )= 2tanθ 1− tan 2 θ . g( θ )= 2tanθ 1− tan 2 θ .$

41.

They are different, try $g( x )= tanx−tan( 2x ) 1+tanxtan( 2x ) . g( x )= tanx−tan( 2x ) 1+tanxtan( 2x ) .$

43.

45.

$1+ 3 2 2 , 1+ 3 2 2 ,$ or 0.9659

47.

$tan( x+ π 4 ) = tanx+tan( π 4 ) 1−tanxtan( π 4 ) = tanx+1 1−tanx(1) = tanx+1 1−tanx tan( x+ π 4 ) = tanx+tan( π 4 ) 1−tanxtan( π 4 ) = tanx+1 1−tanx(1) = tanx+1 1−tanx$

49.

$cos(a+b) cosacosb = cosacosb cosacosb − sinasinb cosacosb = 1−tanatanb cos(a+b) cosacosb = cosacosb cosacosb − sinasinb cosacosb = 1−tanatanb$

51.

$cos(x+h)−cosx h = cosxcosh−sinxsinh−cosx h = cosx(cosh−1)−sinxsinh h = cosx cosh−1 h −sinx sinh h cos(x+h)−cosx h = cosxcosh−sinxsinh−cosx h = cosx(cosh−1)−sinxsinh h = cosx cosh−1 h −sinx sinh h$

53.

True

55.

True. Note that $sin( α+β )=sin( π−γ ) sin( α+β )=sin( π−γ )$ and expand the right hand side.

### 9.3 Section Exercises

1.

Use the Pythagorean identities and isolate the squared term.

3.

$1−cosx sinx , sinx 1+cosx , 1−cosx sinx , sinx 1+cosx ,$ multiplying the top and bottom by $1−cosx 1−cosx$ and $1+cosx , 1+cosx ,$ respectively.

5.

a) $3 7 32 3 7 32$ b) $31 32 31 32$ c) $3 7 31 3 7 31$

7.

a) $3 2 3 2$ b) $− 1 2 − 1 2$ c) $− 3 − 3$

9.

$cosθ=− 2 5 5 ,sinθ= 5 5 ,tanθ=− 1 2 ,cscθ= 5 ,secθ=− 5 2 ,cotθ=−2 cosθ=− 2 5 5 ,sinθ= 5 5 ,tanθ=− 1 2 ,cscθ= 5 ,secθ=− 5 2 ,cotθ=−2$

11.

$2sin( π 2 ) 2sin( π 2 )$

13.

$2− 2 2 2− 2 2$

15.

$2− 3 2 2− 3 2$

17.

$2+ 3 2+ 3$

19.

$−1− 2 −1− 2$

21.

a) $3 13 13 3 13 13$ b) $− 2 13 13 − 2 13 13$ c) $− 3 2 − 3 2$

23.

a) $10 4 10 4$ b) $6 4 6 4$ c) $15 3 15 3$

25.

$120 169 ,– 119 169 ,– 120 119 120 169 ,– 119 169 ,– 120 119$

27.

$2 13 13 , 3 13 13 , 2 3 2 13 13 , 3 13 13 , 2 3$

29.

$cos(74°) cos(74°)$

31.

$cos(18x) cos(18x)$

33.

$3sin(10x) 3sin(10x)$

35.

$−2sin( −x )cos( −x )=−2(−sin( x )cos( x ))=sin( 2x ) −2sin( −x )cos( −x )=−2(−sin( x )cos( x ))=sin( 2x )$

37.

$sin(2θ) 1+cos(2θ) tan 2 θ = 2sin(θ)cos(θ) 1+ cos 2 θ− sin 2 θ tan 2 θ= 2sin(θ)cos(θ) 2 cos 2 θ tan 2 θ = sin(θ) cosθ tan 2 θ= cot(θ) tan 2 θ = tan3 θ sin(2θ) 1+cos(2θ) tan 2 θ = 2sin(θ)cos(θ) 1+ cos 2 θ− sin 2 θ tan 2 θ= 2sin(θ)cos(θ) 2 cos 2 θ tan 2 θ = sin(θ) cosθ tan 2 θ= cot(θ) tan 2 θ = tan3 θ$

39.

$1+cos(12x) 2 1+cos(12x) 2$

41.

$3+cos(12x)−4cos(6x) 8 3+cos(12x)−4cos(6x) 8$

43.

$2+cos(2x)−2cos(4x)−cos(6x) 32 2+cos(2x)−2cos(4x)−cos(6x) 32$

45.

$3+cos(4x)−4cos(2x) 3+cos(4x)+4cos(2x) 3+cos(4x)−4cos(2x) 3+cos(4x)+4cos(2x)$

47.

$1−cos(4x) 8 1−cos(4x) 8$

49.

$3+cos(4x)−4cos(2x) 4(cos(2x)+1) 3+cos(4x)−4cos(2x) 4(cos(2x)+1)$

51.

$( 1+cos( 4x ) )sinx 2 ( 1+cos( 4x ) )sinx 2$

53.

$4sinxcosx( cos 2 x− sin 2 x ) 4sinxcosx( cos 2 x− sin 2 x )$

55.

$2tanx 1+ tan 2 x = 2sinx cosx 1+ sin 2 x cos 2 x = 2sinx cosx cos 2 x+ sin 2 x cos 2 x = 2sinx cosx . cos 2 x 1 =2sinxcosx=sin(2x) 2tanx 1+ tan 2 x = 2sinx cosx 1+ sin 2 x cos 2 x = 2sinx cosx cos 2 x+ sin 2 x cos 2 x = 2sinx cosx . cos 2 x 1 =2sinxcosx=sin(2x)$

57.

$2sinxcosx 2 cos 2 x−1 = sin(2x) cos(2x) =tan(2x) 2sinxcosx 2 cos 2 x−1 = sin(2x) cos(2x) =tan(2x)$

59.

$sin(x+2x) = sinxcos(2x)+sin(2x)cosx = sinx( cos 2 x− sin 2 x )+2sinxcosxcosx = sinx cos 2 x− sin 3 x+2sinx cos 2 x = 3sinx cos 2 x− sin 3 x sin(x+2x) = sinxcos(2x)+sin(2x)cosx = sinx( cos 2 x− sin 2 x )+2sinxcosxcosx = sinx cos 2 x− sin 3 x+2sinx cos 2 x = 3sinx cos 2 x− sin 3 x$

61.

$1+cos(2t) sin(2t)−cost = 1+2 cos 2 t−1 2sintcost−cost = 2 cos 2 t cost(2sint−1) = 2cost 2sint−1 1+cos(2t) sin(2t)−cost = 1+2 cos 2 t−1 2sintcost−cost = 2 cos 2 t cost(2sint−1) = 2cost 2sint−1$

63.

$( cos 2 (4x)− sin 2 (4x)−sin(8x))( cos 2 (4x)− sin 2 (4x)+sin(8x) ) = = (cos(8x)−sin(8x))(cos(8x)+sin(8x)) = cos 2 (8x)− sin 2 (8x) = cos(16x) ( cos 2 (4x)− sin 2 (4x)−sin(8x))( cos 2 (4x)− sin 2 (4x)+sin(8x) ) = = (cos(8x)−sin(8x))(cos(8x)+sin(8x)) = cos 2 (8x)− sin 2 (8x) = cos(16x)$

### 9.4 Section Exercises

1.

Substitute $α α$ into cosine and $β β$ into sine and evaluate.

3.

Answers will vary. There are some equations that involve a sum of two trig expressions where when converted to a product are easier to solve. For example: $sin(3x)+sinx cosx =1. sin(3x)+sinx cosx =1.$ When converting the numerator to a product the equation becomes: $2sin(2x)cosx cosx =1 2sin(2x)cosx cosx =1$

5.

$8( cos( 5x )−cos( 27x ) ) 8( cos( 5x )−cos( 27x ) )$

7.

$sin( 2x )+sin( 8x ) sin( 2x )+sin( 8x )$

9.

$1 2 ( cos( 6x )−cos( 4x ) ) 1 2 ( cos( 6x )−cos( 4x ) )$

11.

$2cos( 5t )cost 2cos( 5t )cost$

13.

$2cos( 7x ) 2cos( 7x )$

15.

$2cos( 6x )cos( 3x ) 2cos( 6x )cos( 3x )$

17.

$1 4 ( 1+ 3 ) 1 4 ( 1+ 3 )$

19.

$1 4 ( 3 −2 ) 1 4 ( 3 −2 )$

21.

$1 4 ( 3 −1 ) 1 4 ( 3 −1 )$

23.

$cos( 80° )−cos( 120° ) cos( 80° )−cos( 120° )$

25.

$1 2 (sin(221°)+sin(205°)) 1 2 (sin(221°)+sin(205°))$

27.

$2 cos( 31° ) 2 cos( 31° )$

29.

$2cos(66.5°)sin(34.5°) 2cos(66.5°)sin(34.5°)$

31.

$2sin( −1.5° )cos( 0.5° ) 2sin( −1.5° )cos( 0.5° )$

33.

$2sin(7x)−2sinx=2sin(4x+3x)−2sin(4x−3x)= 2(sin(4x)cos(3x)+sin(3x)cos(4x))−2(sin(4x)cos(3x)−sin(3x)cos(4x))= 2sin(4x)cos(3x)+2sin(3x)cos(4x))−2sin(4x)cos(3x)+2sin(3x)cos(4x))= 4sin(3x)cos(4x) 2sin(7x)−2sinx=2sin(4x+3x)−2sin(4x−3x)= 2(sin(4x)cos(3x)+sin(3x)cos(4x))−2(sin(4x)cos(3x)−sin(3x)cos(4x))= 2sin(4x)cos(3x)+2sin(3x)cos(4x))−2sin(4x)cos(3x)+2sin(3x)cos(4x))= 4sin(3x)cos(4x)$

35.

$sinx+sin(3x) = 2sin( 4x 2 )cos( −2x 2 )= 2sin(2x)cosx = 2(2sinxcosx)cosx= 4sinx cos 2 x sinx+sin(3x) = 2sin( 4x 2 )cos( −2x 2 )= 2sin(2x)cosx = 2(2sinxcosx)cosx= 4sinx cos 2 x$

37.

$2tanxcos( 3x )= 2sinxcos(3x) cosx = 2(.5(sin(4x)−sin(2x))) cosx = 1 cosx ( sin(4x)−sin(2x) )=secx( sin( 4x )−sin( 2x ) ) 2tanxcos( 3x )= 2sinxcos(3x) cosx = 2(.5(sin(4x)−sin(2x))) cosx = 1 cosx ( sin(4x)−sin(2x) )=secx( sin( 4x )−sin( 2x ) )$

39.

$2cos(35°)cos(23°),1.5081 2cos(35°)cos(23°),1.5081$

41.

$−2sin(33°)sin(11°),−0.2078 −2sin(33°)sin(11°),−0.2078$

43.

$1 2 (cos(99°)−cos(71°)),−0.2410 1 2 (cos(99°)−cos(71°)),−0.2410$

45.

It is an identity.

47.

It is not an identity, but $2 cos 3 x 2 cos 3 x$ is.

49.

$tan( 3t ) tan( 3t )$

51.

$2cos( 2x ) 2cos( 2x )$

53.

$−sin(14x) −sin(14x)$

55.

Start with $cosx+cosy. cosx+cosy.$ Make a substitution and let $x=α+β x=α+β$ and let $y=α−β, y=α−β,$ so $cosx+cosy cosx+cosy$ becomes $cos(α+β)+cos(α−β)=cosαcosβ−sinαsinβ+cosαcosβ+sinαsinβ= 2cosαcosβ cos(α+β)+cos(α−β)=cosαcosβ−sinαsinβ+cosαcosβ+sinαsinβ= 2cosαcosβ$

Since $x=α+β x=α+β$ and $y=α−β, y=α−β,$ we can solve for $α α$ and $β β$ in terms of x and y and substitute in for $2cosαcosβ 2cosαcosβ$ and get $2cos( x+y 2 )cos( x−y 2 ). 2cos( x+y 2 )cos( x−y 2 ).$

57.

$cos( 3x )+cosx cos( 3x )−cosx = 2cos( 2x )cosx −2sin( 2x )sinx =−cot( 2x )cotx cos( 3x )+cosx cos( 3x )−cosx = 2cos( 2x )cosx −2sin( 2x )sinx =−cot( 2x )cotx$

59.

$cos(2y)−cos(4y) sin(2y)+sin(4y) = −2sin(3y)sin(−y) 2sin(3y)cosy = 2sin(3y)sin(y) 2sin(3y)cosy = tany cos(2y)−cos(4y) sin(2y)+sin(4y) = −2sin(3y)sin(−y) 2sin(3y)cosy = 2sin(3y)sin(y) 2sin(3y)cosy = tany$

61.

$cosx−cos( 3x )=−2sin(2x)sin(−x)= 2(2sinxcosx)sinx=4 sin 2 xcosx cosx−cos( 3x )=−2sin(2x)sin(−x)= 2(2sinxcosx)sinx=4 sin 2 xcosx$

63.

$tan( π 4 −t )= tan( π 4 )−tant 1+tan( π 4 )tan(t) = 1−tant 1+tant tan( π 4 −t )= tan( π 4 )−tant 1+tan( π 4 )tan(t) = 1−tant 1+tant$

### 9.5 Section Exercises

1.

There will not always be solutions to trigonometric function equations. For a basic example, $cos(x)=−5. cos(x)=−5.$

3.

If the sine or cosine function has a coefficient of one, isolate the term on one side of the equals sign. If the number it is set equal to has an absolute value less than or equal to one, the equation has solutions, otherwise it does not. If the sine or cosine does not have a coefficient equal to one, still isolate the term but then divide both sides of the equation by the leading coefficient. Then, if the number it is set equal to has an absolute value greater than one, the equation has no solution.

5.

$π 3 , 2π 3 π 3 , 2π 3$

7.

$3π 4 , 5π 4 3π 4 , 5π 4$

9.

$π 4 , 5π 4 π 4 , 5π 4$

11.

$π 4 , 3π 4 , 5π 4 , 7π 4 π 4 , 3π 4 , 5π 4 , 7π 4$

13.

$π 4 , 7π 4 π 4 , 7π 4$

15.

$7π 6 , 11π 6 7π 6 , 11π 6$

17.

$π 18 , 5π 18 , 13π 18 , 17π 18 , 25π 18 , 29π 18 π 18 , 5π 18 , 13π 18 , 17π 18 , 25π 18 , 29π 18$

19.

$3π 12 , 5π 12 , 11π 12 , 13π 12 , 19π 12 , 21π 12 3π 12 , 5π 12 , 11π 12 , 13π 12 , 19π 12 , 21π 12$

21.

$1 6 , 5 6 , 13 6 , 17 6 , 25 6 , 29 6 , 37 6 1 6 , 5 6 , 13 6 , 17 6 , 25 6 , 29 6 , 37 6$

23.

$0, π 3 ,π, 5π 3 0, π 3 ,π, 5π 3$

25.

$π 3 ,π, 5π 3 π 3 ,π, 5π 3$

27.

$π 3 , 3π 2 , 5π 3 π 3 , 3π 2 , 5π 3$

29.

$0,π 0,π$

31.

$π− sin −1 ( − 1 4 ), 7π 6 , 11π 6 ,2π+ sin −1 ( − 1 4 ) π− sin −1 ( − 1 4 ), 7π 6 , 11π 6 ,2π+ sin −1 ( − 1 4 )$

33.

$1 3 ( sin −1 ( 9 10 ) ) 1 3 ( sin −1 ( 9 10 ) )$, $π 3 − 1 3 ( sin −1 ( 9 10 ) ) π 3 − 1 3 ( sin −1 ( 9 10 ) )$, $2π 3 + 1 3 ( sin −1 ( 9 10 ) ) 2π 3 + 1 3 ( sin −1 ( 9 10 ) )$, $π− 1 3 ( sin −1 ( 9 10 ) )π− 1 3 ( sin −1 ( 9 10 ) )$, $4π 3 + 1 3 ( sin −1 ( 9 10 ) ) 4π 3 + 1 3 ( sin −1 ( 9 10 ) )$, $5π 3 − 1 3 ( sin −1 ( 9 10 ) ) 5π 3 − 1 3 ( sin −1 ( 9 10 ) )$

35.

$0 0$

37.

$π 6 , 5π 6 , 7π 6 , 11π 6 π 6 , 5π 6 , 7π 6 , 11π 6$

39.

$3π 2 , π 6 , 5π 6 3π 2 , π 6 , 5π 6$

41.

$0, π 3 ,π, 4π 3 0, π 3 ,π, 4π 3$

43.

There are no solutions.

45.

$cos −1 ( 1 3 ( 1− 7 ) ) cos −1 ( 1 3 ( 1− 7 ) )$, $2π− cos −1 ( 1 3 ( 1− 7 ) ) 2π− cos −1 ( 1 3 ( 1− 7 ) )$

47.

$tan −1 ( 1 2 ( 29 −5 ) ) tan −1 ( 1 2 ( 29 −5 ) )$, $π+ tan −1 ( 1 2 ( − 29 −5 ) )π+ tan −1 ( 1 2 ( − 29 −5 ) )$, $π+ tan −1 ( 1 2 ( 29 −5 ) )π+ tan −1 ( 1 2 ( 29 −5 ) )$, $2π+ tan −1 ( 1 2 ( − 29 −5 ) ) 2π+ tan −1 ( 1 2 ( − 29 −5 ) )$

49.

There are no solutions.

51.

There are no solutions.

53.

$0, 2π 3 , 4π 3 0, 2π 3 , 4π 3$

55.

$π 4 , 3π 4 , 5π 4 , 7π 4 π 4 , 3π 4 , 5π 4 , 7π 4$

57.

$sin −1 ( 3 5 ), π 2 ,π− sin −1 ( 3 5 ), 3π 2 sin −1 ( 3 5 ), π 2 ,π− sin −1 ( 3 5 ), 3π 2$

59.

$cos −1 ( − 1 4 ),2π− cos −1 ( − 1 4 ) cos −1 ( − 1 4 ),2π− cos −1 ( − 1 4 )$

61.

$π 3 π 3$, $cos −1 ( − 3 4 ) cos −1 ( − 3 4 )$, $2π− cos −1 ( − 3 4 )2π− cos −1 ( − 3 4 )$, $5π 3 5π 3$

63.

$cos −1 ( 3 4 ) cos −1 ( 3 4 )$, $cos −1 ( − 2 3 ) cos −1 ( − 2 3 )$, $2π− cos −1 ( − 2 3 )2π− cos −1 ( − 2 3 )$, $2π− cos −1 ( 3 4 ) 2π− cos −1 ( 3 4 )$

65.

$0, π 2 ,π, 3π 2 0, π 2 ,π, 3π 2$

67.

$π 3 π 3$, $cos −1 ( − 1 4 ) cos −1 ( − 1 4 )$, $2π− cos −1 ( − 1 4 )2π− cos −1 ( − 1 4 )$, $5π 3 5π 3$

69.

There are no solutions.

71.

$π+ tan −1 ( −2 ) π+ tan −1 ( −2 )$, $π+ tan −1 ( − 3 2 )π+ tan −1 ( − 3 2 )$, $2π+ tan −1 ( −2 )2π+ tan −1 ( −2 )$, $2π+ tan −1 ( − 3 2 ) 2π+ tan −1 ( − 3 2 )$

73.

$2πk+0.2734,2πk+2.8682 2πk+0.2734,2πk+2.8682$

75.

$πk−0.3277 πk−0.3277$

77.

$0.6694,1.8287,3.8110,4.9703 0.6694,1.8287,3.8110,4.9703$

79.

$1.0472,3.1416,5.2360 1.0472,3.1416,5.2360$

81.

$0.5326,1.7648,3.6742,4.9064 0.5326,1.7648,3.6742,4.9064$

83.

$sin −1 ( 1 4 ),π− sin −1 ( 1 4 ), 3π 2 sin −1 ( 1 4 ),π− sin −1 ( 1 4 ), 3π 2$

85.

$π 2 , 3π 2 π 2 , 3π 2$

87.

There are no solutions.

89.

$0, π 2 ,π, 3π 2 0, π 2 ,π, 3π 2$

91.

There are no solutions.

93.

$7.2 ∘ 7.2 ∘$

95.

$5.7 ∘ 5.7 ∘$

97.

$82.4 ∘ 82.4 ∘$

99.

$31.0 ∘ 31.0 ∘$

101.

$88.7 ∘ 88.7 ∘$

103.

$59.0 ∘ 59.0 ∘$

105.

$36.9 ∘ 36.9 ∘$

### Review Exercises

1.

$sin −1 ( 3 3 ) sin −1 ( 3 3 )$, $π− sin −1 ( 3 3 )π− sin −1 ( 3 3 )$, $π+ sin −1 ( 3 3 )π+ sin −1 ( 3 3 )$, $2π− sin −1 ( 3 3 ) 2π− sin −1 ( 3 3 )$

3.

$7π 6 , 11π 6 7π 6 , 11π 6$

5.

$sin −1 ( 1 4 ),π− sin −1 ( 1 4 ) sin −1 ( 1 4 ),π− sin −1 ( 1 4 )$

7.

$1 1$

9.

Yes

11.

$−2− 3 −2− 3$

13.

$2 2 2 2$

15.

$cos(4x)−cos(3x)cosx = cos(2x+2x)−cos(x+2x)cosx = cos(2x)cos(2x)−sin(2x)sin(2x)−cosxcos(2x)cosx+sinxsin(2x)cosx = ( cos 2 x− sin 2 x ) 2 −4 cos 2 x sin 2 x− cos 2 x( cos 2 x− sin 2 x )+sinx(2)sinxcosxcosx = ( cos 2 x− sin 2 x ) 2 −4 cos 2 x sin 2 x− cos 2 x( cos 2 x− sin 2 x )+2 sin 2 x cos 2 x = cos 4 x−2 cos 2 x sin 2 x+ sin 4 x−4 cos 2 x sin 2 x− cos 4 x+ cos 2 x sin 2 x+2 sin 2 x cos 2 x = sin 4 x−4 cos 2 x sin 2 x+ cos 2 x sin 2 x = sin 2 x( sin 2 x+ cos 2 x )−4 cos 2 x sin 2 x = sin 2 x−4 cos 2 x sin 2 x cos(4x)−cos(3x)cosx = cos(2x+2x)−cos(x+2x)cosx = cos(2x)cos(2x)−sin(2x)sin(2x)−cosxcos(2x)cosx+sinxsin(2x)cosx = ( cos 2 x− sin 2 x ) 2 −4 cos 2 x sin 2 x− cos 2 x( cos 2 x− sin 2 x )+sinx(2)sinxcosxcosx = ( cos 2 x− sin 2 x ) 2 −4 cos 2 x sin 2 x− cos 2 x( cos 2 x− sin 2 x )+2 sin 2 x cos 2 x = cos 4 x−2 cos 2 x sin 2 x+ sin 4 x−4 cos 2 x sin 2 x− cos 4 x+ cos 2 x sin 2 x+2 sin 2 x cos 2 x = sin 4 x−4 cos 2 x sin 2 x+ cos 2 x sin 2 x = sin 2 x( sin 2 x+ cos 2 x )−4 cos 2 x sin 2 x = sin 2 x−4 cos 2 x sin 2 x$

17.

$tan( 5 8 x ) tan( 5 8 x )$

19.

$3 3 3 3$

21.

$− 24 25 ,− 7 25 , 24 7 − 24 25 ,− 7 25 , 24 7$

23.

$2( 2+ 2 ) 2( 2+ 2 )$

25.

$2 10 , 7 2 10 , 1 7 , 3 5 , 4 5 , 3 4 2 10 , 7 2 10 , 1 7 , 3 5 , 4 5 , 3 4$

27.

$cotxcos(2x) = cotx( 1−2 sin 2 x ) = cotx− cosx sinx (2) sin 2 x = −2sinxcosx+cotx = −sin(2x)+cotx cotxcos(2x) = cotx( 1−2 sin 2 x ) = cotx− cosx sinx (2) sin 2 x = −2sinxcosx+cotx = −sin(2x)+cotx$

29.

$10sinx−5sin( 3x )+sin( 5x ) 8( cos( 2x )+1 ) 10sinx−5sin( 3x )+sin( 5x ) 8( cos( 2x )+1 )$

31.

$3 2 3 2$

33.

$− 2 2 − 2 2$

35.

$1 2 ( sin(6x)+sin(12x) ) 1 2 ( sin(6x)+sin(12x) )$

37.

$2sin( 13 2 x )cos( 9 2 x ) 2sin( 13 2 x )cos( 9 2 x )$

39.

$3π 4 , 7π 4 3π 4 , 7π 4$

41.

$0, π 6 , 5π 6 ,π 0, π 6 , 5π 6 ,π$

43.

$3π 2 3π 2$

45.

No solution

47.

$0.2527,2.8889,4.7124 0.2527,2.8889,4.7124$

49.

$1.3694,1.9106,4.3726,4.9137 1.3694,1.9106,4.3726,4.9137$

### Practice Test

1.

1

3.

$sec( θ ) sec( θ )$

5.

$2 − 6 4 2 − 6 4$

7.

$− 2 − 3 − 2 − 3$

9.

$− 1 2 cos θ + 3 2 sin θ − 1 2 cos θ + 3 2 sin θ$

11.

$1−cos( 64 ∘ ) 2 1−cos( 64 ∘ ) 2$

13.

$0,π 0,π$

15.

$π2,3π2 π2,3π2$

17.

$2cos(3x)cos(5x)2cos(3x)cos(5x)$

19.

$4sin( 2θ )cos( 6θ ) 4sin( 2θ )cos( 6θ )$

21.

$x=cos–1 (15) x=cos–1 (15)$

23.

$π3 π3$

25.

$35 , – 45 , – 34 35 , – 45 , – 34$

27.

$tan3x–tanxsec2x =tanx(tan2x–sec2x) =tanx(tan2x–(1+tan2x)) =tanx(tan2x–1–tan2x) =–tanx=tan(–x)=tan(–x) tan3x–tanxsec2x =tanx(tan2x–sec2x) =tanx(tan2x–(1+tan2x)) =tanx(tan2x–1–tan2x) =–tanx=tan(–x)=tan(–x)$

29.

$sin(2x) sinx– cos(2x) cosx = 2sinxcosx sinx – 2cos2x–1cosx = 2cosx–2cosx+1cosx = 1cosx =secx=secx sin(2x) sinx– cos(2x) cosx = 2sinxcosx sinx – 2cos2x–1cosx = 2cosx–2cosx+1cosx = 1cosx =secx=secx$

31.

Amplitude: $1414$ , period: $160160$ , frequency: 60 Hz

33.

Amplitude: 8, fast period: $15001500$ , fast frequency: 500 Hz, slow period: $110110$ , slow frequency: 10 Hz

35.

$D(t)=20(0.9086)t cos(4πt) D(t)=20(0.9086)t cos(4πt)$ , 31 second

Order a print copy

As an Amazon Associate we earn from qualifying purchases.